Polyethylene glycol in spinal cord injury repair: a critical review - Lu X; Perera TH; Aria AB; Smith Callahan LA (Dove Medical Press, 2018)
Xi Lu,* T Hiran Perera,* Alexander B Aria, Laura A Smith Callahan Department of Neurosurgery, Center for Stem Cells and Regenerative Medicine, University of Texas Health Science Center at Houston, Houston, TX, USA *These authors contributed equally to this work Abstract: Polyethylene glycol (PEG) is a synthetic biocompatible polymer with many useful properties for developing therapeutics to treat spinal cord injury. Direct application of PEG as a fusogen to the injury site can repair cell membranes, mitigate oxidative stress, and promote axonal regeneration to restore motor function. PEG can be covalently or noncovalently conjugated to proteins, peptides, and nanoparticles to limit their clearance by the reticuloendothelial system, reduce their immunogenicity, and facilitate crossing the blood–brain barrier. Cross-linking PEG produces hydrogels that can act as delivery vehicles for bioactive molecules including growth factors and cells such as bone marrow stromal cells, which can modulate the inflammatory response and support neural tissue regeneration. PEG hydrogels can be cross-linked in vitro or delivered as an injectable formulation that can gel in situ at the site of injury. Chemical and mechanical properties of PEG hydrogels are tunable and must be optimized for creating the most favorable delivery environment. Peptides mimicking extracellular matrix protein such as laminin and n-cadherin can be incorporated into PEG hydrogels to promote neural differentiation and axonal extensions. Different hydrogel cross-linking densities and stiffness will also affect the differentiation process. PEG hydrogels with a gradient of peptide concentrations or Young’s modulus have been developed to systematically study these factors. This review will describe these and other recent advancements of PEG in the field of spinal cord injury in greater detail. Keywords: combinatorial methods, hydrogel, regenerative medicine, nanoparticles, fusogen, drug delivery